DIFFERENCES IN THE LEVEL OF SITUATIONAL -MOTOR ABILITIES OF FOOTBALL PLAYERS OF DIFFERENT LEVEL COMPETITIONS - Omer Špirtović; Danilo Aćimović; Aleksandar Joksimović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
The study was conducted on 170 subjects, football players - senior citizens, aged 18-27 years from the territory of Montenegro.Utilizes a system of 16 variables, situational-motor abilities. Our aim was to determine the discriminatory ability of their rank according to the modalities of which belong to the players tested (second and third league competitions). Results of canonical discriminant analysis of the players in situational-motor variables that belong to different ranks of the competitions, significant at the .00 level. Therefore, we can speak of two quantitatively and qualitatively different groups of patients.